Information and dispatch system of the CarTrace transport company based on the GPS technology - Есилевский, В.С.; Губочкин, В.И. (Radiotekhnika, 2012)
The major organizational and technical problems associated with increasing the efficiency of trucking companies are discussed, methods of their solution through the introduction of low-cost, quick-payback information and dispatch system based on GPS-technology are considered.